Second allogeneic haematopoietic cell transplantation using HLA‐matched unrelated versus T‐cell replete haploidentical donor and survival in relapsed acute myeloid leukaemia. (10th April 2021) - Kharfan‐Dabaja, Mohamed A.; Labopin, Myriam; Brissot, Eolia; Kroger, Nicolaus; Finke, Jürgen; Ciceri, Fabio; Deconinck, Eric; Blaise, Didier; Chevallier, Patrice; Gramatzki, Martin; Ganser, Arnold; Stelljes, Matthias; et al.
Summary: Optimal donor choice for a second allogeneic haematopoietic cell transplant (allo‐HCT) in relapsed acute myeloid leukaemia (AML) remains unknown. We compared overall survival (OS) using registry data from the Acute Leukemia Working Party (ALWP) of the European Society for Blood and Marrow Transplantation (EBMT) involving 455 adults who received a second allo‐HCT from a human leucocyte antigen (HLA)‐matched unrelated (MUD) ( n = 320) or a haploidentical ( n = 135) donor. Eligibility criteria required adults aged ≥18 years who received a second allo‐HCT for treating AML relapse between 2005 and 2019. The primary end‐point was OS. There was no statistically significant difference in the median (interquartile range) age between the groups, MUD 46 (35–58) versus haploidentical 44 (33–53) years ( P = 0·07). The median OS was not different between the MUD and the haploidentical groups (10 vs. 11 months, P = 0·57). Similarly, the 2‐year OS was 31% for the MUD and 29% for the haploidentical donor groups. The OS was worse if the procedure was performed with active AML [hazard ratio (HR) 1·42, 95% confidence interval (CI) 1·07–1·89; P = 0·02]. Conversely, a longer time from first allo‐HCT to relapse (>13·2 months) was associated with better OS (HR 0·50, 95% CI 0·37–0·69; P < 0·0001). The results of the present analysis limit the ability to recommend one donor type over another when considering a second allo‐HCT for relapsed AML. Our findings highlight that best OS is achieved when receiving the second allo‐HCT in complete remission.